2018
DOI: 10.20944/preprints201805.0060.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Concrete Properties Comparison When Substituting a 25% Cement with Slag from Different Provenances

Abstract: Concrete consumption greatly exceeds the use of any other material in engineering. This is due to its good properties as construction material and the availability of its components. Nevertheless, the present worldwide construction increase and the high-energy consumption for cement production means a high environmental impact. On the other hand, one of the main problem in iron and steel industry is waste generation and by-products that must be properly processed or reused to promote the environmental sustaina… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Selected studies [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] of numerous recent research works reported to the scientific journal Materials were devoted to the use and incorporation of steel slags in road construction materials and concrete. The BOF slag incorporated in the asphalt mixture is advantageous for improving the ability of this mixed material to resist the deformation and enhancing the stability of structure, according to Ye et al [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selected studies [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] of numerous recent research works reported to the scientific journal Materials were devoted to the use and incorporation of steel slags in road construction materials and concrete. The BOF slag incorporated in the asphalt mixture is advantageous for improving the ability of this mixed material to resist the deformation and enhancing the stability of structure, according to Ye et al [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parron-Rubio et al [ 16 ] reported replacing cement by 25% slag, which is considered to be a good strategy for reducing cement consumption and solving the waste problem. The use of steel slag as a partial replacement for cement could make a significant contribution to the steel industry and help to reduce CO 2 emissions [ 17 ].…”
Section: Introductionmentioning
confidence: 99%